Susceptibility of contemporary single-bottle self-etch dentine adhesives to intrinsic water permeation - Pucci, Cesar R. [UNESP]; Gu, Li-Sha; Zeng, Chang; Gou, Ya-Ping; Tay, Franklin R.; Niu, Li-Na (Elsevier, 2017)
Objectives To evaluate the effect of intrinsic water permeation on the microtensile bond strengths of different adhesive systems to dentine and the quality of resin-dentine interfaces. Methods Ninety-six non-carious human third molars were divided into 4 groups: Clearfil S3 Bond Plus (CSBP; Kuraray); Clearfil S3 Bond (C3S; Kuraray); iBond Self-Etch (IB; Heraeus-Kulzer) and Prime&Bond NT (PB, control etch-and-rinse adhesive, Dentply-Sirona). For each adhesive, specimens from one subgroup (N = 10) were bonded using zero pulpal pressure, while specimens from the other subgroup (N = 10) were bonded using 15 cm water pressure (PP). Each bonded tooth was sectioned into 1 × 1 mm sticks and stressed to failure. Data were analysed using two-way ANOVA and Holm-Sidak pairwise comparisons to examine the effects of “adhesive”, “pulpal pressure” and their interaction on bond strength (α = 0.05). Representative fractured sticks were examined by SEM. The remaining tooth slabs in each subgroup were used for TEM and CLSM. Results Microtensile bond strengths (mean ± SD; in MPa) were: 33.4 ± 6.9 (CSBP), 33.2 ± 4.7 (CSBP-PP), 35.0 ± 8.6 (C3S), 25.5 ± 7.3 (C3S-PP), 18.4 ± 4.0 (IB), 16.5 ± 6.9 (IB-PP), 28.2 ± 5.5 (PB), 20.5 ± 7.2 (PB-PP). “Adhesive-type” (P < 0.001), “pulpal-pressure” (P < 0.001) and their interactions (P < 0.001) significantly affected bond strength results. No difference between no-PP and PP subgroups was found for CSBP and IB (P > 0.05). Water droplets were identified along the resin-dentine interface for IB, IB-PP and C3S-PP. Conclusion IB exhibits water sensitivity when bonding is performed with/without pulpal pressure. C3S exhibits water sensitivity when bonding is performed with pulpal pressure. CSBP does not exhibit water sensitivity when bonding is performed with/without pulpal pressure. Clinical significance: Intrinsic water permeation during bonding procedures significantly affects bond strength results and the resin-dentine interface of contemporary single-bottle self-etch dentine adhesive systems.
Keywords: Bond strength; Degradation; Dentine bonding agents; Dentine permeability; Hybrid layer; Pulpal pressure